Up-Regulation of Tmevpg1 and Rmrp LncRNA Levels in Splenocytes and Brain of Mouse with Experimental Autoimmune Encephalomyelitis - Farahani, E; Sotoodehnejadnematalahi, F; Mami, S; Fathollahi, A; Hajimolahoseini, M; Pouriran, R; Yeganeh, Farshid (Novelty in Biomedicine, 2019)
Background: Two long noncoding (lnc) RNAs, which have been recognized as Tmevpg1/Ifng-AS1/NeST and Rmrp play indispensable roles in the differentiation of TH1 and TH17, respectively. The aim of the present scientific study was to analyze the expression levels of the aforementioned lncRNAs in experimental autoimmune encephalomyelitis (EAE) as an animal model for multiple sclerosis (MS). Materials and Methods: Initially, EAE was induced in C57BL/6 mice via immunization by using MOG peptide. The leukocyte infiltration rate and demyelination of neuronal axons were determined. Secondly, the expression levels of Tmevpg1, Rmrp, Tbx21, and Rorc were analyzed in the cultured splenocytes and brain lysates, by using Real-Time PCR assay; eventually, the levels of interferon-gamma and interleukin-17 evaluated by ELISA. Results: Gene expression analysis revealed that Rorc expression in the splenocytes of EAE mice in comparison to the controls was elevated; however, Tbx21 expression did not show any significant difference. Tmevpg1 and Rmrp levels increased in the splenocytes of EAE mice (4.48 times and 39.70 times, respectively, p = 0.0001). Besides, in the brain lysate, the entire genes that have been mentioned were higher than the controls (Tmevpg1: 3.35 times p = 0.02 and Rmrp 11.21 times, p = 0.0001). Conclusion: The marked up-regulation in Tmevpg1 and Rmrp transcripts suggested the essential roles of lncRNAs in the pathogenesis of EAE and multiple sclerosis indeed. Further investigations are necessary to evaluate the values of these lncRNAs as the target for the therapy or molecular marker for disease monitoring.